Among stand heterogeneity is key for biodiversity in managed beech forests but does not question the value of unmanaged forests: Response to Bruun and Heilmann‐Clausen (2021). Issue 9 (31st August 2021) - Schall, Peter; Heinrichs, Steffi; Ammer, Christian; Ayasse, Manfred; Boch, Steffen; Buscot, François; Fischer, Markus; Goldmann, Kezia; Overmann, Jörg; Schulze, Ernst‐Detlef; Sikorski, Johannes; Weisser, Wolfgang W.; et al.
Abstract: Schall et al. (2020) assessed how a combination of different forest management systems in managed forest landscapes dominated by European beech may affect the biodiversity (alpha, beta and gamma) of 14 taxonomic groups. Current forest policy and nature conservation often demand for combining uneven‐aged managed and unmanaged, set‐aside for nature conservation, beech forests in order to promote biodiversity. In contrast to this, Schall et al. (2020) found even‐aged shelterwood forests, represented by different developmental phases, to support highest regional (gamma) diversity. By pointing out that unmanaged forests included in our study are not old‐growth forests, Bruun and Heilmann‐Clausen (2021) challenge our conclusion as not providing sound scientific advice to societies. It is true that the studied unmanaged forests are not representing old‐growth forests as defined in the literature. However, we demonstrate the representativeness of our unmanaged forests for current beech forest landscapes of Central Europe, where managed forests were more or less recently set‐aside in order to develop old‐growth structures. We also show that the managed and recently unmanaged forests in our study already differ distinctively in their forest structures. We use this response to stress the role of forest reserves for promoting certain species groups, and to emphasise their importance as valuable research sites today and in the future. Synthesis and applications . We see two main conclusions from our study. First, unmanaged forests still matter. We agree with Bruun and Heilmann‐Clausen (2021) on the general importance of unmanaged, old‐growth or long‐untouched forests, and we do not question the importance of set‐aside forests for biodiversity conservation. However, a complete complementarity to managed systems may only reveal after many decades of natural development. Second, safeguarding biodiversity in largely managed forest landscapes should focus on providing a landscape matrix of different developmental phases with varying environmental conditions rather than on maximising the vertical structure within stands. Such landscapes can partly compensate for structures that are still missing in vital, dense and closed forests recently set‐aside or for unsuitable phases that may occur due to a cyclic synchronisation of forest structures in unmanaged forests. Abstract : We see two main conclusions from our study. First, unmanaged forests still matter. We agree with Bruun and Heilmann‐Clausen (2021) on the general importance of unmanaged, old‐growth or long‐untouched forests, and we do not question the importance of set‐aside forests for biodiversity conservation. However, a complete complementarity to managed systems may only reveal after many decades of natural development. Second, safeguarding biodiversity in largely managed forest landscapes should focus on providing a landscape matrix of different developmental phases with varying environmental conditions rather than on maximising the vertical structure within stands. Such landscapes can partly compensate for structures that are still missing in vital, dense and closed forests recently set‐aside or for unsuitable phases that may occur due to a cyclic synchronisation of forest structures in unmanaged forests.